SPINAL CORD STIMULATION (SCS): TECHNICAL ASPECTS AND NEW DIRECTIONS - Julia Wilanowska; Jędrzej Sztajura; Wiktoria Mikulska; Kamila Tasior (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and purpose: Spinal cord stimulation (SCS) is a well-established implantable neuromodulation therapy for chronic pain. Over the last decade, the field has evolved rapidly due to the diversification of stimulation waveforms, expanded programming capabilities, and the emergence of data-driven paradigms such as ECAP-controlled closed-loop systems. This review aims to present SCS as a medico-technical system by summarizing key mechanisms of neuromodulation, core elements of system architecture, clinical indications and selection principles, and technological directions. Materials and methods: A comprehensive literature search was performed using PubMed, BioMed Central, Scopus, and Google Scholar to identify relevant studies on spinal cord stimulation. The search included the following keywords and their combinations: spinal cord stimulation, SCS, neuromodulation, chronic pain, failed back surgery syndrome, and complex regional pain syndrome. Results: Evidence supports that SCS analgesia arises from both segmental spinal mechanisms and supraspinal modulation, with waveform-dependent differences in sensory and affective pain processing. Modern SCS platforms integrate leads, IPG, and telemetry/programming layers, enabling multipolar field shaping and increasingly incorporating sensing channels for objective biomarkers (e.g., ECAP) and real-time dose stabilization. Indications remain centered on PSPS/FBSS and CRPS, with expanding applications across selected neuropathic pain syndromes. Conclusion: SCS is transitioning from conventional open-loop neuromodulation toward biomarker-driven, adaptive, and remotely supported therapy. Future progress is likely to be shaped by closed-loop architectures, improved sensing and telemetry, and computational approaches enabling more consistent outcomes and scalable personalization.